HPLC-UV method development and validation for anticancer drug sorafenib and the co-prescribed drug dexamethasone: application to pharmacokinetic evaluation of sorafenib nanoformulations - Mateen, Abdul; Khan, Abad; Khan, Ismail; Khalil, Saifullah Khan; Ahmad, Lateef; Junaid, Muhammad; Jehan, Saqib; Anwar, Muhammad Sohail; Faheem, Muhammad; Salam, Abdul (Frontiers in Pharmacology, 2025)
Sorafenib is used to treat advanced renal cell carcinoma. A high-performance liquid chromatography (HPLC) method was developed for the simultaneous determination of sorafenib with a commonly co-prescribed drug, dexamethasone, using meloxicam as an internal standard. The separation was achieved with acetonitrile and water with 0.05% trifluoroacetic acid (TFA), 65:35 v/v, eluted at 1.0 mL/min at a wavelength of 265 nm. The chromatographic separation was carried out on an ACE Generic C18 (5 μm, 4.6 mm × 150 mm, UK) column by injecting a sample volume of 20 µL into the HPLC system. The analytes were extracted with acetonitrile using the protein precipitation method. The chromatographic parameters were optimized, and the method was validated as per the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines. The internal standard concentration was kept constant (1.0 μg/mL) in all samples. The method was linear for both sorafenib and dexamethasone in the concentration ranges of 25–1,000 ng/mL and 50–2,000 ng/mL, respectively, with a correlation coefficient (r2) of 0.999 for both the analytes. The target compounds were well resolved within 8 min. The limits of detection (LODs) are 9 ng/mL and 14 ng/mL, while the limits of quantification (LOQs) are 26 ng/mL and 47 ng/mL for sorafenib and dexamethasone, respectively. The method was found to be accurate and precise with a percentage relative standard deviation (RSD) of less than ±15. The method was successfully applied to evaluate the pharmacokinetics of a sorafenib nanoformulation and a conventional formulation. The AUC0-t was significantly increased for the sorafenib nanoformulation (129.8 ± 1.54 µg-hrml−1) compared to the conventional formulation (15.0 ± 0.014 µg-hrml−1), while clearance was reduced for the sorafenib nanoformulation (31.551 ± 0.007 mlh−1kg−1) compared with the conventional formulation (426.856 ± 0.098 mlh−1kg−1).